Hubungan Lingkungan Kerja dengan Motivasi Kerja Karyawan Toko Indomaret - Krisnawanto, Dhika Arsela; , Dra. Partini, M. Si (2016)
The purpose of this study to determine whether there is a relationship between work environment with motivation to work . This research subject Indomaret amounted to 100 employees who are still working. Sampling technique using cluster random sampling with purposive sampling technique. The method used in this research is quantitative method measuring devices such scale work environment and work motivation scale. Data analysis techniques used in this study is from the Pearson product moment correlation using SPSS (Statistical Program for Social Sciene) 16.0 For Windowas Program. Based on the analysis of data obtained by the correlation coefficient r = 0.612 with sig = 0.000 (p <0.01), which means there is a relationship between the working environment and work motivation. Work environment variables included in the high category, while the motivation to work in the category of being.